2006
DOI: 10.2471/blt.05.027037
|View full text |Cite
|
Sign up to set email alerts
|

Methods for establishing a surveillance system for cardiovascular diseases in Indian industrial populations

Abstract: Objective To establish a surveillance network for cardiovascular diseases (CVD) risk factors in industrial settings and estimate the risk factor burden using standardized tools. Methods We conducted a baseline cross-sectional survey (as part of a CVD surveillance programme) of industrial populations from 10 companies across India, situated in close proximity to medical colleges that served as study centres. The study subjects were employees (selected by age and sex stratified random sampling) and their family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
132
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 16 publications
(19 reference statements)
9
132
2
Order By: Relevance
“…These estimates are lower than those reported in two studies from rural Andhra Pradesh. 4,11 Another multi-centric study among industrial worker families, 12 (age 20e69 years) also reported that40% of all participants were exposed to tobacco and about 30%had central obesity. The prevalence of known hypertension in this study was similar to that in our study (10%), while that of incident hypertension was lower (30%).…”
Section: Discussionmentioning
confidence: 99%
“…These estimates are lower than those reported in two studies from rural Andhra Pradesh. 4,11 Another multi-centric study among industrial worker families, 12 (age 20e69 years) also reported that40% of all participants were exposed to tobacco and about 30%had central obesity. The prevalence of known hypertension in this study was similar to that in our study (10%), while that of incident hypertension was lower (30%).…”
Section: Discussionmentioning
confidence: 99%
“…[14,15,16,17] Among 131 males in this study, 46 were tobacco smokers and of them, 10 persons were diabetic but this association was not found to be significant. This is similar to the findings in several studies [14,16,17,21] It was observed that in our study, 42% of the male participants had a history of alcohol consumption and of them, 16 (21.1%) had diabetes. This association was not found to be significant.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated very high levels of CVD risk factors among a relatively young population from 10 industrial settings across India [7].…”
mentioning
confidence: 99%
“…The prevalence of MS among South Asians is higher than in other Asians and Europeans [6].In India, CVD is projected to be the largest cause of death and disability by 2020, with 2.6 million Indians predicted to die due to coronary heart disease, which constitutes 54.1% of all CVD deaths [7].…”
mentioning
confidence: 99%